Combination of Anti-programmed Cell Death Protein 1 and Antiangiogenesis Displaying a Response Disparity between Pulmonary and Nonpulmonary Metastases - Bing-Syuan Chung; Peng-Chan Lin; Shang-Hung Chen; Yu-Min Yeh (Journal of Cancer Research and Practice)
Targeting the vascular endothelial growth factor-mediated immune suppression is a strategy to overcome the resistance of anti-programmed cell death protein 1/programmed death-ligand 1 (anti-PD-1/PD-L1) therapy. Here, we present two cases, including one case with leiomyosarcoma and the other one with microsatellite-stable colorectal cancer, receiving the combination of pembrolizumab and lenvatinib as salvage treatment. Both cases demonstrated a significant response in lung metastases; however, the nonpulmonary metastases progressed. These findings suggest that lung metastasis might have a distinct tumor immune microenvironment, and further studies to investigate the efficacy of PD-1/PD-L1-based combination therapy in patients with lung-limited metastases are warranted.